An Analysis of Students’ Self-efficacy In Writing at MAN 1 Padusunan - Yolanda Dian Safitri; Delvi Wahyuni (Journal of English Language Teaching, 2022)
The analysis of students' writing skills at MAN 1 Padusunan. This study intends to show how students' self-efficacy was in writing English language learning at State MAN 1 Padusunan. The researcher utilized SPSS 22.0 and Microsoft Excel to analyze the data for this descriptive qualitative research study. Six courses were randomly chosen to make up the 87 student study samples. The research's data came from a survey given to grade X students at MAN 1 Padusunan. According to the data analysis, the majority of students (56.3%) fell into the category of medium level selfefficacy in English writing. Some of them (43.7%) pupils had the highest degree of self-efficacy in learning the English language, while (0%) of the students had the lowest level. Based on the study's findings, it can be said that State MAN 1 Padusunan students had a medium level of self-efficacy.